Promoting Critical Thinking through an Interdisciplinary Study Abroad Program - Cai, WeiWei; Sankaran, Gopal (Journal of International Students, 2015)
This paper discusses the promotion of critical thinking through an interdisciplinary curriculum design using multidisciplinary faculty as well as details the implementation of an experiential short-term study abroad program in China. To achieve this educational goal of critical thinking, along with meeting the requirements specific to each course, the program was built on a framework using two interrelated approaches – theme-based interdisciplinary curriculum and cultural immersion. The theme-based interdisciplinary curriculum was constructed on three principles (the ability to pose great questions that encompassed drawing knowledge and skills from each discipline, acquiring global awareness, and developing glocal awareness). Cultural immersion was accomplished through carefully selected site visits, activities, and assignments. Students’ experiences, reflections, and applications were assessed through formative and summative evaluation.